Bureaucratic delay, local-level monitoring, and delivery of small infrastructure projects: Evidence from a field experiment in Bolivia - Monica Yanez-Pagans; Carlos Gustavo Machicado (Institute for the Study of Labor (IZA), 2012)
This paper examines bureaucratic delay within the allocation of small infrastructure projects by sub-municipal governments in Bolivia, and it presents a randomized field experiment designed to improve public service delivery by promoting voice, transparency, and accountability among grassroots organizations. The experiment consists of randomly providing sub-municipal governments with a mailing tracking system, which provides public officials and grassroots organizations real- time information about the processing of small infrastructure projects requests by sub-municipal governments. The objective of this intervention is twofold. First, is to facilitate the involvement of grassroots organizations in the process of reviewing, tracking, and monitoring small infrastructure project allocations. Second, is to explicitly alter the probability of detecting inefficient administrative practices within district councils and, therefore, to implicitly increase the expected cost of engaging in such practices among public officials. The findings of this paper suggest that monitoring tools that promote access to information by citizens might play a critical role in improving public service delivery outcomes. Yet, in settings where mechanisms of local accountability are subject to be captured by local elites or are weak, monitoring tools might have limited capacity to improve outcomes. In such settings, major transparency related reforms might be needed to improve public service delivery outcomes.
Keywords: D73; C93; H76; 330; Bolivia; transparency; accountability; local-level monitoring; bureaucratic delay; Kommunale Infrastruktur; Infrastrukturpolitik; Bürokratie; Bürgerbeteiligung; Bolivien